Effects of creatine supplementation on body composition exercisers practitioners - Miranda Oliveira, Ludmila (2017)
Objective: To investigate the effects of creatine supplementation on body composition exercisers practitioners. Materials and methods: This is a literature review that in your selection process were analyzed 26 articles, nine deleted and consists of 17 national and international articles, one legislation and one research in a book, published between the years 2000-2014. Results and Discussion: Were analyzed experimental studies with creatine and placebo and sampling was selective, mostly, with physically active individuals of both sexes and animals models. The protocol for the studies was different supplementation ranging from 3g to 430g having the period from six days to 12 days. Conclusion: Most studies have shown that creatine supplementation showed positive results in anaerobic performance, increase in percentage of maximum strength, decreased fatigue and increased lean mass. Its use appears to be more effective in high-intensity exercise, short with small intervals between sets.